Adult non-urethral complications after hypospadias repair in childhood: presentation, treatment and outcomes - Stojanovic, Borko; Bizic, Marta; Bencic, Marko; Djordjevic, Miroslav L. (Frontiers in Endocrinology, 2023)
Purpose: This study aimed to evaluate a group of adult patients with non-urethral complications after hypospadias repair in childhood, their surgical treatment, and outcomes. Materials and Methods: We analyzed 97 patients, mean age 22.5 years, who were treated in our center between January 2009 and December 2020, for non-urethral complications after previous hypospadias repair in childhood. Non-urethral complications were defined as glans deformity, residual curvature and trapped penis due to insufficient penile skin. A radical surgical approach was used to correct all deformities, in a one-stage or a two-stage procedure. A successful outcome was defined as a straight penis with good length, anatomically regular glans, and cosmetically acceptable appearance, without need for additional surgeries. Sexual function was evaluated using International Index of Erectile Function. Results: Mean follow-up was 75 months (ranged from 24 to 168 months). One-stage and two-stage repair were performed in 85.5% and 14.5% of cases, respectively. A higher success rate was noted after one-stage repair (94% compared to 86%). Complications included four cases of penile curvature with late onset, one case of glans dehiscence and partial skin necrosis. Erectile dysfunction was determined in 24% of patients. Discussion: Non-urethral complications may occur many years after primary hypospadias repair, with a strong impact on the quality of life. Treatment is individualized and usually involves a radical surgical approach to correct all associated deformities and to achieve successful cosmetic and psychosexual outcomes.